High performance work systems in emergent organizations: Implications for firm performance - Messersmith, Jake G.; Guthrie, James P. (Human Resource Management, 2010)
AbstractEmerging firms are the foundation for economic growth in today's business world. Yet relatively little is known about the factors that contribute to the success or failure of developing organizations. This research study addresses this broad question by examining the role that high performance work systems (HPWS) play in the performance of high‐tech new ventures. Using the resource‐based and dynamic capability perspectives, this research project examines the links between HPWS and firm performance. Results indicate that HPWS utilization is positively associated with sales growth and innovation; however, a hypothesized mediating role for employee voluntary turn over was not supported. © 2010 Wiley Periodicals, Inc.